Attributions of Negative Partner Behaviour by Men who Physically Abuse Their Partners - Tonizzo, Santina (1996)
Conflict in close relationships is associated with specific patterns of attributions (Bradbury & Fincham 1990). The objective of this study was to investigate If violence would be associated with particular type of attributions made for negative partner behaviours. Three groups of men were classified using the Conflict Tactics Scale (CTS; Straus, 1979) as physically violent (in Domestic Violence Intervention Progams), (n = 19), non-physically violent in (counselling), ( n = 17), and non-physically violent in the (community), (n = 31 ). The Relationship Attribution Measure (RAM) by Fincham & Bradbury, ( 1992) was used to assess the attributional dependent variables of locus, stability, globality, intent, motivation and blame. A one-way MANOVA revealed a significant overall difference on the six attributional dimensions between the physically violent and non physically violent men. Post hoc comparisons showed that physically violent men were more likely than the non physically violent men (counselling) to attribute the negative behaviour of their partners to unchangeable, intentional rather than unintentional, selfishly motivated and blameworthy causes. Further, the physically violent men were more likely than the non-physically violent (community) to make attributions that globally affected other areas of the relationship, as well as attributing their negative partner's behaviour to be intentional, selfish and blameworthy. When the effect of marital satisfaction was controlled using a one-way MANCOV A, the group difference on attributional measures disappeared. This suggested that marital satisfaction was likely to account for the attributional differences between the groups, rather than the violence per se. Practical implications for men in Domestic Violence Intervention Programs are suggested. A number of methodological issues arc discussed and directions for future research arc considere